The effect of pseudoephedrine on self-paced endurance cycling performance - Betteridge, S.; Mündel, T.; Stannard, S. (European Journal of Sport Science, 2010)
The purpose of this study was to investigate the effects of pseudoephedrine ingestion on endurance cycling performance. Using a double-blind, randomized cross-over design, eight well-trained cyclists (VO2max=69±2 ml · kg-1 · min-1) performed two self-paced performance time-trials in the laboratory at least 6 days apart. Ninety minutes before the trial, the participants consumed either placebo or pseudoephedrine (2.5 mg · kg-1bw). The time-trial required completion of a set amount of work, equivalent to riding at 150 min at a power output calculated to elicit 70% VO2max. Venous blood samples were collected just before starting the trial, then at every 20% increment completed work until the required work was completed. Although time to complete the trial was quicker for five of the eight participants, there was no significant effect of pseudoephedrine on performance (P=0.235), or blood glucose or lactate, between trials. However, heart rate was significantly higher with pseudoephedrine consumption compared with placebo (P< 0.05). The results of this study indicate that pseudoephedrine has no effect on self-paced endurance exercise performance, but may affect the cardiac response to exercise.